FROM IDEA TO PRACTICE - BRUSSELS AGREEMENT KOSOVO - METOHIJA EVERYDAY LIFE (Heritage, 2020)
SUMMARYIn this paper we are analyzing the idea of the Brusseles agreement as a political idea which was suposed to normalize ethnic realtions between Serbia and „Kosovo“, with everyday ethnic realtions in the Kosovo and Metohija region. According to documents from „ Republic od Serbia’s report on the progress in the Belgrade - Pristina dialogue“, there is visible contradictionfor the reader where progress in the dialogue in Brusseles resulted in regression in ethnic realtions. On the account of numeros acts of violenc by albanian extremists to sebian minorty, such as house burning, rapeing, kidnapping women and children and tearing down religious and cultural monuments thruout the Brusseles agreement, with benevolent watch international community and EU, comes the conclusion that the agreement is mildly said an insufficient solution for the kosovo situation. Besides that, constant outbursts of violence explicitly on serbian people, with elements of destroying serbian nationality. Subsequetnlysaying, this problem demands compromised solution with effective participation of the International community in finding a solution.
Keywords: Brusseles agreement; Serbia; “Kosovo”; Kosovo and Metohija; conflicts; organized violence.